2022
DOI: 10.1080/14756366.2021.2024526
|View full text |Cite
|
Sign up to set email alerts
|

Research progress of coumarins and their derivatives in the treatment of diabetes

Abstract: Diabetes is a group of metabolic diseases characterised by chronic hyperglycaemia caused by multiple causes, which is caused by insulin secretion and/or utilisation defects. It is characterised by increased fasting and postprandial blood glucose levels due to insulin deficiency or insulin resistance. It is reported that the harm of diabetes mainly comes from its complications, and the cardiovascular disease caused by diabetes is the primary cause of its harm. China has the largest number of diabetic patients i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 91 publications
0
12
0
Order By: Relevance
“…The rapid increase of diabetes and its underlying patients led to a substantial increase in the number of diabetic cardiovascular complications ( 98 ). In fact, the effect of diabetes on atherosclerotic VSMCs is not simply regulated by a certain mechanism, but the result of the interaction of multiple factors ( 99 ).…”
Section: Diabetes and Vsmcsmentioning
confidence: 99%
“…The rapid increase of diabetes and its underlying patients led to a substantial increase in the number of diabetic cardiovascular complications ( 98 ). In fact, the effect of diabetes on atherosclerotic VSMCs is not simply regulated by a certain mechanism, but the result of the interaction of multiple factors ( 99 ).…”
Section: Diabetes and Vsmcsmentioning
confidence: 99%
“…Coumarin rings are present in many bioactive compounds, which are widely found in nature as well as in biologically active new synthetic compounds [ 9 ]. These heterocyclic compounds exhibit a range of important pharmacological and biological activities, such as antidiabetic [ 10 ], anticancer [ 11 ], antifungal [ 12 ], and antibacterial [ 13 ] activity. Many derivatives containing coumarin ring display multifunctional bioactivity [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many derivatives containing coumarin ring display multifunctional bioactivity [ 6 ]. A variety of coumarin derivatives with antidiabetic activity have been designed and synthesized as well as isolated from plants, in particular, for the treatment of Type 2 diabetes mellitus [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, some studies have shown that some natural compounds have the effects of lowering blood glucose, lowering blood lipid and anti-oxidation, and have good effects in the treatment of diabetes complications [ 13 , 14 ]. In this review, we searched the PubMed database and Google scholar with “(Diabetes nephropathy) OR (Diabetic kidney disease)”, found a recently published article on the treatment of DKD with a natural compound, and then searched with “((Diabetes nephropathy) OR (Diabetic kidney disease)) AND (compound)” to find all the studies on the treatment of DKD with this compound, and selected articles with in-depth mechanism research for review.…”
Section: Introductionmentioning
confidence: 99%